BIO552: Analytical Biochemistry / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This course focuses on techniques for the preparation, qualitative analysis, quantitative analysis of proteins and other biomolecules. The analytical techniques covered in this course include chromatography, electrophoresis, spectroscopy and mass spectrometry. Current issues related to application of these techniques in modern bio science research will be addressed. The outcomes of this course will be assessed through a variety of tools including the traditional final examination, tests, quizzes, assignments and lab reports. This course is essential for students intending a career as a laboratory technologist or research scientist in the areas of biochemistry, biotechnology and molecular biology.